Analisis Eksperimental Prinsip Keseimbangan Benda Tegar Menggunakan Alat Peraga Sistem Balok dan Pivot sebagai Media Pembelajaran Fisika - Anggia; Monica Amelia; Erlida (Universitas Garut, 2025)
This study aims to experimentally analyze the principle of rigid body equilibrium using a beam and pivot system as a learning aid. The concept of rigid body equilibrium explains how forces and moments work to keep an object stable. In this study, an experimental method with a quantitative approach was used to verify the law of force-moment equilibrium through variations in mass and the distance of the load from the fulcrum. The tools used included a wooden beam as a rigid body, a pivot as a fulcrum, and metal loads with varying masses. The results show that equilibrium is achieved when the left and right moments have almost the same value, with an average moment difference of <0.002 Nm. which shows high consistency with the theory of ∑τ = 0. In addition, the position of the center of mass which is within the range of ±0.3 cm from the fulcrum confirms the achievement of stable equilibrium. These findings indicate that the beam-pivot teaching aid is effective for use as a learning medium because it is able to visualize the relationship between mass, distance, and torque in a concrete manner, thereby helping to reduce misconceptions regarding the direction of rotation and moment of force. The implication of this research is that the design of a simple tool such as the beam-pivot system can be used as a reference in the development of educational experimental devices that are inexpensive, easy to implement, and relevant to strengthen the understanding of basic concepts in physics learning.